Institucionalização da fisioterapia no Brasil: um estudo sobre o processo na Paraíba - Vieira, Risomar da Silva (2011)
The interest for the study of the theme institutionalization of Physiotherapy in Brazil and in particular in Paraíba still represents an embryonic experience, considering the expressive quantity of studies referent to other fields of knowledge in health. Obviously in some states of the country there already appear studies about the historic process of Physiotherapy, however in Paraíba it can be said that investigations in this area are still constituted as a vacuum to be studied. In view of this scenario, the present study aimed by an overview about the trajectory of Physiotherapy in the international and Brazilian environment, to analyze the process of institutionalization of this knowledge in health in the Paraíba space. For the making of the study primary and secondary sources were visited including in this construction the resource of Oral History as a possibility of discoveries. At the conclusion of the activity it was verified by the examined material that Physiotherapy in Paraíba in the course of its effectuation as profession and field of knowledge, as in other places, suffered favorable and unfavorable influence of cultural social-political and epidemiologic factors, taking into consideration the specificity of each location